Reconstruction of the tax dispute resolution system to achieve legal justice in Indonesia - Hutagalung, Hermansyah (Priviet Social Sciences Journal, 2025)
The tax dispute resolution system in Indonesia plays a strategic role in maintaining a balance between the interests of tax authorities and the rights of taxpayers as part of the principle of legal justice in a country governed by the rule of law. However, the current system still faces various problems, including overlapping authorities between the Directorate General of Taxes and the Tax Court, the institutional dependence of the Tax Court on the Ministry of Finance, and a lengthy settlement process that often causes legal uncertainty for taxpayers. This situation indicates the need to reconstruct the tax dispute resolution system to make it more independent, efficient, and oriented towards substantive justice. This study uses a normative juridical method with a statute, conceptual, and comparative approach. The analysis is conducted on legal norms governing tax courts and dispute resolution practices in several comparative countries. The results show that the tax dispute resolution system in Indonesia does not fully reflect the principles of the rule of law and legal justice as mandated by Article 24 of the 1945 Constitution. Reconstruction is needed by strengthening the institutional position of the Tax Court under the Supreme Court, establishing an Alternative Dispute Resolution (ADR) mechanism for tax disputes, simplifying the objection and appeal processes, and digitizing tax court administration. Through these measures, it is hoped that the tax dispute resolution system in Indonesia can better guarantee certainty, fairness and legal protection for all parties.